Preferences for home delivery in Ethiopia: provider perspectives. - Sipsma, Heather; Thompson, Jennifer; Maurer, Lydia; Bradley, Elizabeth; Curry, Leslie (Global public health, 2013)
More than half of the maternal deaths worldwide occur in sub-Saharan Africa, most commonly during childbirth or the immediate post-partum period. Although delivery in health care facilities can avert maternal deaths, many women in sub-Saharan Africa continue to deliver at home. Factors influencing mothers' decisions to use facility-based delivery services in rural, low-income settings are not well understood. Health care professionals who provide delivery services in these areas may have unique insights about factors specific to such settings. Accordingly, we conducted a qualitative study of health care professionals in rural Ethiopia to determine key factors influencing facility delivery, using in-depth interviews and the constant comparative method of data analysis. Results suggest multiple influences on women's decisions to deliver at home, including inadequate resources in facilities; unappealing aspects of delivery in facility settings; and known barriers to accessing services such as distance, transportation and cost. Our findings suggest that local health care providers offer valuable insight into why many rural Ethiopian women deliver their babies at home, despite major efforts to promote facility-based delivery. Their perspectives underscore the importance of a patient-centred approach to delivery services, which is often lacking in low-resource settings but may be fundamental to encouraging facility-based deliveries.
Keywords: Ethiopia; Female; Health Personnel; Home Childbirth; Humans; Maternal Health Services; Maternal Mortality; Maternal Welfare; Patient Preference; Pregnancy; Professional-Patient Relations; Qualitative Research; Rural Population